An ever more entangled Union? The European Union's interactions with global governance institutions. Issue 5 (4th July 2022) - Marx, Axel; Westerwinter, Oliver
ABSTRACT: Contemporary global governance is characterized by a diversity of institutions. The European Union (EU) interacts with these institutions in multiple ways. Despite their importance, the interactions of the EU with different types of global governance institutions have remained underexplored in EU scholarship. The papers in this special issue address this research gap. They map the EU's interactions with different types of global governance institutions. They also explore the factors that explain patterns of interactions. In this introduction, we develop a common analytical lens that unites the contributions to the special issue and identify our main research questions. We map different types of global governance institutions and discuss the ways in which the EU interacts with them. We also bring together the main insights from the individual contributions and discuss avenues for future research.